PTH(1‐84) replacement therapy in hypoparathyroidism: A randomized controlled trial on pharmacokinetic and dynamic effects after 6 months of treatment. (18th September 2013) - Sikjaer, Tanja; Amstrup, Anne Kristine; Rolighed, Lars; Kjaer, Soren Geill; Mosekilde, Leif; Rejnmark, Lars
ABSTRACT: Untreated, hypoparathyroidism (hypoPT) is a state of hypocalcemia with inappropriately low plasma parathyroid hormone (PTH) levels and hyperphosphatemia. PTH administration normalizes plasma calcium and phosphate levels and reduces the doses of calcium and active vitamin D analogues needed. To develop an evidence‐based clinical algorithm to monitor hypoPT patients treated with recombinant human PTH (rhPTH[1‐84]) injected subcutaneously in the thigh, we performed a 24‐hour monitoring study of pharmacokinetic and pharmacodynamic effects in a group of 38 patients who had completed a 6‐month randomized study on effects of treatment with a fixed rhPTH(1‐84) dose of 100 µg/d or similar placebo as an add‐on to conventional treatment. PTH levels rose immediately, reaching a median peak level of 26.5 (interquartile range [IQR], 20.1–42.5) pmol/L 15 minutes following injection. Thereafter, levels gradually decreased until reaching predosing levels after 16 hours, with a plasma half‐life of 2.2 (1.7–2.5) hours. rhPTH(1‐84) changed the diurnal rhythms of ionized calcium levels and 1, 25‐dihydroxyvitamin D (1, 25[OH]2 D) levels, with rising levels following injection. Ionized calcium peaked after 7.0 (5.0–10.0) hours. Asymptomatic hypercalcemia was present in 71% of the rhPTH(1‐84)‐treated patients. Compared with placebo, 24‐hour urinary calcium, phosphate, and magnesium did not change, although the diurnal variation in renal excretion rates changed significantly in response to treatment. In conclusion, as a safety precaution, we recommend occasionally measuring calcium levels at approximately 7 hours after administration in order to reveal episodes of hypercalcemia. A 100‐µg daily dose of rhPTH(1‐84) appears to be too high in some patients, suggesting a need for a device allowing for individual dose adjustments. © 2013 American Society for Bone and Mineral Research.